Investor demand, size effect and performance of Malaysian Initial Public Offerings: evidence from Post-1997 financial crisis - Othman Yong (Penerbit Universiti Kebangsaan Malaysia, 2007)
This paper examines the initial performance of 185 Malaysian Initial Public Offerings (IPOs) from January 1999 to December 2003. The study finds that the average initial return of the 185 Malaysian IPOs is markedly lower (but still under-priced) than any other average initial return before the 1997 financial crisis reported by previous studies; the same is true for the average over-subscription ratio. IPOs listed on the Second Board and Mesdaq generate higher initial returns than their counterparts listed on the Main Board, giving support to size effect hypothesis. Overall, with the exception of public issue, the average initial return (offer-to-close) is lower than the average initial return (offer-to-open), that seems to suggest that an investor is better off disposing his IPO at the beginning of the first day of trading. In general. the average over-subscription ratio for IPOs listed on Mesdaq is the highest, followed by the Second Board and the lowest is the Main Board. In general, only investor demand (as represented by over-subscription ratio) can explain (on a consistent basis) the levels of initial return of Malaysian IPOs.